Identification and antimicrobial activity of Micromonospora strains from Thai peat swamp forest soils - Chitti Thawai, Pawina Kanchanasin, Moriya Ohkuma, Takuji Kudo, Somboon Tanasupawat (Journal of Applied Pharmaceutical Science, 2018)
The identification and antimicrobial activity of thirteen actinomycete strains isolated from peat swamp forest soils collected from Narathiwat, Patthaloong and Yala provinces, the southern part of Thailand were carried out. Based on the phenotypic and chemotaxonomic characteristics, all isolates were belonged to genus Micromonospora. They were separated into six groups based on 16S ribosomal RNA gene sequence analysis and were identified as M. narathiwatensis (Group 1, 5 isolates), M. humi (Group 4, 3 isolates), M. aurantiaca (Group 5, 2 isolates), one of each isolate as M. chalcea (Group 2) and M. maritima (Group 6). The isolate LK6-12 (Group 3) showed low similarity (99.16%) with the type strains of Micromonospora siamensis that will be the novel species of the genus Micromonospora. Meso-diaminopimelic acid (cell wall type II), xylose and arabinose (pattern D) were detected in their whole-cell hydrolysates. The major polar lipid was phosphatidylethanolamine (type II). The predominant cellular fatty acids were C17:0, C17:1ω8c, iso-C16:0, iso-C15:0, iso-C17:0, anteiso-C15:0, and anteiso-C17:0. The predominant menaquinones were MK-9(H4), MK-9(H6), or MK-10(H4). The DNA G+C contents of the isolates ranged from 71.6- 72.6 mol%. On the primary screening, 2 isolates exhibited the antimicrobial activity against Bacillus subtilis ATCC 6633 and Kocuria rhizophila ATCC 9341.
Keywords: Actinomycetes, antimicrobial activity, Thai peat swamp forest, soils, Micromonospora.